String's the thing: oxford literacy web - Graham, Elspeth; Newsham, Ian (Oxford University Press Hong kong, 1999)
Part of The Oxford Literacy Web, a literacy programme designed to guide schools through the primary years, this title features stories and illustrations to talk about early school experiences. It talks about Mrs Best's reception class and about the Year 1 class and their teacher, Mr Jelly, while Cheep, the baby bird finds a friend in Josh.